Characterisation of viscoelastic response of swollen elastomers / Mahak Fazal - Mahak, Fazal (2013)
Given the wide energy insecurity crisis in the world, alternative fuels are fast becoming the most sought after means of providing energy. This is relevant to the fast growing population and fast depletion of conventional energy resources. However the practical application of these alternative fuels can only be possible if they are compatible with the materials, in particular elastomers, used in service conditions. Keeping this in view, the present study focuses on the compatibility of elastomers and palm biodiesel. More precisely, the swelling characteristics of elastomers in palm biodiesel in the absence and in the presence of static mechanical loading are investigated. For this purpose, Nitrile Butadiene Rubber (NBR) with three different carbon black contents is considered: 0, 25 and 40 wt%. Moreover, the resulting mechanical responses of swollen NBR are probed through a set of mechanical testing. The emphasis is laid on the effect of swelling on the viscoelastic response of elastomers. Results show that the swelling of NBR is reduced by the introduction of carbon black filler, i.e. carbon black provides resistance to deterioration due to exposure to aggressive liquid. Furthermore, independently of the carbon content, the presence of static tensile strain appears to increase the swelling for shorter durations of immersion. For longer immersion durations, the degree of swelling remains generally unaffected by the presence of uniaxial strain. Finally, mechanical testing results show that the viscoelastic response of elastomers unaffected by the swelling degree. However, by comparing the hysteresis curves for elastomers under different swelling levels, viscoelasticity appears to decrease with increase in swelling level.